Effectiveness of Left Judkins Catheter as a Single Multipurpose Catheter in Transradial Coronary Angiography From Right Radial Artery: A Randomized Comparison With Conventional Two‐Catheter Strategy. (1st March 2016) - Turan, Burak; Erkol, Ayhan; Mutlu, Ayhan; Daşli, Tolga; Erden, İsmail
Abstract : Objectives: To investigate safety and efficacy of left Judkins (JL) catheter as a single multipurpose catheter in transradial coronary angiography (TRA). Background: Most operators use standard femoral catheters instead of special multipurpose transradial catheters during TRA. Methods: Patients undergoing TRA through right radial artery (RRA) were randomized into single‐catheter approach with JL3.5 and two‐catheter approach with JL3.5 and right Judkins 4.0 catheters. Primary outcome measures were rate of success in selective and stable engagement of both coronary arteries with JL catheter, procedure and fluoroscopy times. Results: Of 314 patients enrolled, 206 patients (aged 60.3 ± 12.4 years, 36.9% female) were randomized. JL3.5 was successful in 66.0% of patients as a single catheter. Additional catheter was needed more frequently in single‐catheter group (34 vs. 0.97%, P < 0.001). Single‐catheter approach reduced procedure time significantly (6.7 ± 2.1 vs. 7.9 ± 3.3 minutes, P = 0.002). However on average there was 19.7% relative increase in fluoroscopy time (2.61 ± 1.38 vs. 2.18 ± 1.54 minutes, P = 0.035) with single‐catheter approach. Radial artery spasm tended to develop more frequently in two‐catheter group (22.3 vs. 12.6%, P = 0.067). In nearly half of the patients, procedure had been completed successfully with JL3.5 catheter within a fluoroscopy time similar to that of two‐catheter group. Conclusion: In TRA from RRA, JL3.5 catheter can be very effective when dedicated multipurpose catheter is not available. As a single multipurpose catheter, JL works perfectly in nearly half of procedures without prolonging procedure and fluoroscopy times. However insisting on a single‐catheter approach with JL could unnecessarily increase fluoroscopy time and, hence, radiation exposure. (J Interven Cardiol 2016;29:257–264)